Politeness Strategies in Model Conversations in English Textbooks for Elementary School Students - Sugeng Purwanto; Liliek Soepriatmadji (Master Program in Linguistics, Diponegoro University, 2013)
The study investigated to what extent politeness strategies had been integrated in the conversation models in five English textbooks for Grade- 6 Elementary School Students. In the study, each ‘move’ in the conversations was matched against the criteria for politeness strategies (Leech 1983). The results show that politeness strategies have been adopted in the five books under study with the most significant use of non FTA. However, there were also uses of varying degrees of FTA. Thus, the teachers should be selective in using the textbooks and there should be a cooperation among those involved in supplying school textbooks. Penelitian ini mengkaji seberapa jauh ‘strategi kesantuan’ diintegrasikan dalam model konversasi yang disajikan di tiga buah buku teks bahasa Inggris bagi Siswa Sekolah Dasar, Kelas 6. Dalam penelitian ini, masing-masing langkah (move) di konversasi dicocokkan dengan criteria strategi kesopanan (Leech 1983). Hasil penelitian menunjukkan bahwa strategi kesopanan telah diadopsi ke dalam kelima buku yang diteliti dengan penggunaan non FTA yang sangat signifikan, dan hanya sedikit yang menggunakan FTA dengan tingkat yang berbeda. Dengan demikian, para guru harus selektif dalam menggunakan buku-buku teks dan harus ada kerjasama bagi yang terlibat dalam menyediakan buku-buku sekolah.